Electronic Public Relations in Islamic Education Institutions - Robbi Rodliyya; Maharrany Subekti Putri; Prayoga Tata Pribadi; Khusnul Khotimah (Yayasan Adra Karima Hubbi, 2024)
Background. The rapid development of information technology has brought significant changes to the practice of Public Relations, from the conventional era to the digital era. New challenges emerge, including the need for faster and more efficient information and communication. The use of gadgets and the internet makes it easier to communicate without time and space boundaries, forcing public relations practitioners to adapt to these developments. Therefore, public relations must follow digital trends to remain relevant and effective in carrying out their duties. Purpose. The purpose of writing this study is to discuss what electronic public relations is. Cyber ??public relations or electronic public relations is a new concept where in its implementation public relations uses online-based media. There are many benefits that can be taken from electronic public relations, one of which is building relationships between organizations and the public effectively and efficiently. Method. This research method uses library research methods. The library research method is a study that studies various reference books and the results of previous research which is useful for obtaining a theoretical basis regarding the problem to be researched. The theoretical basis used is taken from e-journals, e-books, and script files. The theoretical basis that has been obtained is used as material to compile this study. Results. The results of implementing Electronic Public Relations (E-PR) in educational institutions show improvements in various aspects of communication and institutional image management. E-PR allows educational institutions to communicate more quickly and efficiently with their public without being bound by time and space constraints. With unlimited internet access, institutions can convey information anytime and anywhere. Conclusion. The conclusion of this research is that Electronic Public Relations (E-PR) in educational institutions increases the effectiveness of communication and builds a positive image with the public through digital media. E-PR enables faster and more efficient two-way interactions, while saving operational costs. Even though it provides many benefits, challenges such as data security, credibility, and technology adaptation must still be considered. Good management can overcome these challenges and improve the institution’s reputation. Overall, E-PR is an important tool in facing the development of the digital era in educational institution public relations.